SISTEM PENDUKUNG KEPUTUSAN UNTUK MEMILIH MOBIL BEKAS DI FAMILY GARAGES DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Ahmad Ferdiyansyah; Ahmad Suryadi; Budi Santoso (Journal of Information System, Informatics and Computing, 2026)
This research aims to develop a Decision Support System (DSS) to assist consumers and management at Family Garages in selecting the best second-hand cars in an objective and systematic manner. The system is designed using the Simple Additive Weighting (SAW) method, which effectively processes various important criteria such as price, production year, engine condition, mileage, and fuel consumption. With this system, the car selection process, which was previously manual and subjective, can now be carried out based on structured calculations that provide more accurate recommendations according to user preferences. Additionally, the system aims to improve decision-making efficiency and support Family Garages in providing better services to customers. It is expected that the implementation of this system will lead to more accurate, efficient decisions in purchasing second-hand cars, reducing the risk of errors in car selection. The system also has the potential to increase customer satisfaction and trust in the services provided by Family Garages.